PENGARUH PROFITABILITAS, UMUR PERUSAHAAN, STRUKTUR KEPEMILIKAN INSTITUSIONAL DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI - Desy Mariani (Universitas Budi Luhur, 2021)
This research is conducted to analyze the influence of profitability, age of the company, institutional ownership, company size of capital structure. The population in this research is used secondary data from the financial statement of sub sector property and real estate companies listed in the Indonesia Stock Exchange in 2015-2019 as many as 30 companies for sample. The data analysis used double linear regression analysis with program SPSS version 20.0. The result of this research show that profitability has a positive and significant effect on capital structure, the age of the company does not affect the capital structure. While institutional ownership and company size have a negative and significant effect on capital structure.